Andrew Marvell and Constantijn Huygens: Common Grounds and Mutual Contacts. Issue 1 (15th February 2018) - Huysman, Ineke
Abstract : This paper compares the somewhat parallel lives of Constantijn Huygens and Andrew Marvell, but it also examines their differences and asks whether there may actually have been encounters between the two of them. One of their mutual contacts was the English priest Richard Flecknoe, who was an agent in the service of Béatrix de Cusance, Duchess of Lorraine, in which capacity he came into contact with both Huygens and Marvell. This essay also explains the context around Flecknoe's poverty, which Marvell writes about in his satirical poem 'Flecknoe an English Priest at Rome'.